The Effects of Shading and Organic Domestic Waste on Brazilian Spinach Growth - Linda Sulistiani; Zaidan P. Negara; Fikri Adriansyah; Fitra Gustiar; Entis Sutisna Halimi; Erizal Sodikin; Strayker Ali Muda (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2023)
The use of household waste in the form of rice washing water, pineapple skin waste, and leftover rice as liquid organic fertilizer (LOF) has the potential to create a good growing medium so as to increase plant growth. Brazilian Spinach (Alternanthera sissoo) is a leafy vegetable that has the potential to diversify vegetable consumption in urban areas where it is expected to grow well in tight spaces, particularly under shading. This study aimed to find out the effects of applying liquid organic fertilizer made of household waste and the shading on the growth of the Brazilian spinach plant. The study used a split plot design with a main plot consisted of 0%, 50% and 70% shading, while subplot consisted of LOF washing water (20 ml/l), pineapple peel waste (30 ml/l) and leftover rice (50ml/l). Each treatment was repeated 3 (three) times. The results of the study showed that the SPAD value of Brazilian spinach under shading treatment and LOF treatment of rice washing water linearly continued to increase until 8 (eight) weeks after planting. Regarding the vegetative growth of Brazilian spinach, the 0% shading treatment was the best treatment in terms of increasing the non-edible leaf fresh weight and root dry weight. Meanwhile, the LOF had an insignificant effect on all treatments. In conclusion, Brazilian spinach can grow more optimally in no-shade conditions.